PRE- AND POST-INFECTIONAL RESISTANCE OF SWEET POTATO TO Meloidogyne incognita and M. javanica - Gapasin, Ruben M. (Annals of Tropical Research, 1986)
Pre-infectional resistance was indicated by fewer nematodes which penetrated the resistant cultivars Jasper, Jewel and W-86 compared to those which entered the susceptible cultivars Binicol and UPR. Post-infectional resistance was shown by delayed or retarded development of nematodes after penetration in Jasper and Jewel or to non-development to maturity in W-86. The number of eggs per egg mass and the size of egg-laying females in susceptible cultivars were significantly greater that those in resistant cultivars Jasper and Jewel.